Surgical site infection in adult patients after heart procedures: an integrative review - Bruno Henrique Fiorin; Beatriz Costa; Lucas Dalvi Armond Rezende; Alcy Leal Aranha; Bruna Moraes Barbieri; Walckiria Garcia Romero Sipolatti; Rita Simone Lopes Moreira (Universidade Federal do Ceará, 2022)
Objective: to identify the risk factors for surgical site infection in patients after heart procedure. Methods: integrative literature review by searching the Medical Literature Analyses and Retrieval System online, Latin American and Caribbean Literature on Health Sciences, Scientific Electronic Library Online, Nursing Database. The search for the articles occurred during the month of February 2022. Results: 24 articles were eligible for the review. In all studies, the population was mostly male, aged between 51 and 70 years, who underwent elective myocardial revascularization surgery. The main comorbidities presented were diabetes mellitus, hypertension, and obesity. The infection rates ranged from 2.4% to 38.9%, and the main pathogen identified was Staphylococcus aureus. Conclusion: the main comorbidities present in patients who manifested surgical site infection were diabetes, hypertension, obesity, and smoking. The risk factors were gender, age, and prolonged preoperative hospitalization. Antibiotic prophylaxis, trichotomy, nasal decolonization, and adequate skin antisepsis were the most adopted prophylactic measures. Contributions to practice: knowing the profile of patients who developed infection may favor planning risk control actions.